A retrospective study on the efficacy of Ninjin'yoeito on fatigue in patients with interstitial pneumonia. (October 2021) - Kushima, Hisako; Kinoshita, Yoshiaki; Fujita, Masaki; Ishii, Hiroshi
Abstract: Introduction: Fatigue, caused by dyspnea associated with progression of interstitial pneumonia (IP), can negatively affect patients' quality of life (QOL). Ninjin'yoeito (NYT), a Chinese herbal medicine, is prescribed for general symptoms of fatigue and for fatigue associated with various respiratory diseases. However, there is a lack of integrated research on the effects of NYT in patients with IP. Therefore, we retrospectively investigated the efficacy of NYT in patients with IP and fatigue. Materials and methods: From the IP patients who had taken NYT, 19 who met the following inclusion criteria were included: (1) age of ≥20 years, (2) fatigue, and (3) history of NYT administration. The primary endpoint was fatigue, which was assessed using the Chalder Fatigue Scale (CFS). The secondary endpoints were loss of appetite and dyspnea, which were evaluated using the Simplified Nutritional Appetite Questionnaire (SNAQ) and modified Medical Research Council (mMRC) scores, respectively. All items were measured before and after 12 weeks of NYT administration. Results: In the enrolled 19 patients (male, 12; female, 7; mean age, 65.8 ± 12.7 years), the underlying diseases were idiopathic pulmonary fibrosis ( n  = 8), idiopathic pleuroparenchymal fibroelastosis ( n  = 5), connective tissue disease-related interstitial pneumonia ( n  = 2), chronic hypersensitivity pneumonitis ( n  = 3), and nonspecific interstitial pneumonia ( n  = 1). The CFS score decreased from 17.1 ± 6.8 before administration to 13.4 ± 5.7 after administration of NYT ( p  = 0.0389). The SNAQ score did not change markedly. The median mMRC score decreased from 3 to 2, however, the difference was not significant. Conclusion: Many subtypes of IP are progressive, and a cure cannot be expected in cases of irreversible lung fibrosis. Therefore, a multifaceted approach to improve and maintain the QOL is needed in addition to the standard of care. This study showed that NYT can improve fatigue and help maintain the QOL in IP patients.